A NEW INTERPRETATIONAL NARRATIVE OF DAGH’S POETRY - Dr. Muhammad Rauf; Dr. Sajid Javed (Zaban-o-Adab, 2022)
When Mirza Ghalib gave up entertaining Urdu ghazal under the suppression of colonial regime, Mirza Khan Dagh proved to be his true replacement. He fully expressed the contemporary socio-political consciousness in his poetic works through particular erotic suggestion system of this genre. But ironically, applying the western critical parameters introduced by the colonial discourse, he was supposed to be vulgar and sex-oriented, paying no heed to the rich in between meanings of his pregnant couplets. In this research paper, a new interpretational reading of Dagh’s poetry and its findings have been discussed according to which he proves to be the most vibrant interpreter of his colonial era.